2015
DOI: 10.1007/s10453-015-9372-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological contamination in the work environments of museums, archives and libraries

Abstract: Museums, archives and libraries have large working environments. The goal of this study was to determine microbial contamination in these work places and estimate the influence of microclimatic parameters and total dust content on microbial contamination. In addition, research included evaluation of ergosterol concentration and fungal bioaerosol particle size distribution. Numbers of micro-organisms in the air and on the surfaces in museums were higher (2.1 × 102–7.0 × 103 cfu/m3 and 1.4 × 102–1.7 × 104 cfu/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 24 publications
1
50
0
5
Order By: Relevance
“…Species of Aspergillus, Penicillium and Cladosporium with aerodynamic diameters less than 8 µm were found in high percentage in air of museum store room, indicated that fungi found as single cells, spores or small fragments of mycelium (Skóra et al, 2015) It is important to sample microbial particles as size fractions, since particles with smaller diameters are more likely to enter the lungs and thus may negatively impact human health. Fine size microbial fractions are able to penetrate the respiratory system of human, causing irritation to mucous membrane of nose and eyes, inflammatory responses and allergic reactions (Kulkarni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Species of Aspergillus, Penicillium and Cladosporium with aerodynamic diameters less than 8 µm were found in high percentage in air of museum store room, indicated that fungi found as single cells, spores or small fragments of mycelium (Skóra et al, 2015) It is important to sample microbial particles as size fractions, since particles with smaller diameters are more likely to enter the lungs and thus may negatively impact human health. Fine size microbial fractions are able to penetrate the respiratory system of human, causing irritation to mucous membrane of nose and eyes, inflammatory responses and allergic reactions (Kulkarni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Borrego and Perdomo (2012) found that Gram positive cocci and bacilli bacteria are abundant in libraries in Cuba. Moreover, species of Micrococcus (Harkawy et al, 2011), Staphylococcus (Hayleeyesus and Manaye, 2014) and Bacillus (Skóra et al, 2015) were found to be the common bacterial genera in indoors environment of libraries and archives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karbowska-Berentet al (2011), mencionam que livros e outros materiais de arquivo são ricos reservatórios de nutrientes, principalmente celulose que é o principal componente do papel e proteínas que estão presentes na cola e adesivos usados na manufatura do produto. Esses nutrientes estimulam o crescimento de grupos específicos de microrganismos, dentre eles os fungos que exibem propriedades celulolítica (Trichoderma, Penicillium, Botrytis, Chaetomium, Stemphyliume Alternaria) Na literatura, há vários estudos que investigam a microbiota fúngica e bacteriana em bibliotecas públicas (GAMBALE et al 1993, KARBOWSKA-BERENT et al 2011PANTOJA et al 2012;MICHELUZ et al 2015;SKÓRA et al 2015).…”
Section: Introductionunclassified